Chronic exposure to yttrium induced cell apoptosis in the testis by mediating Ca2+/IP3R1/CaMKII signaling - Liu, Zhehao; Ding, Yechun; Xie, Shuchun; Hu, Yaqiong; Xiao, Hai; Liu, Xia; Fan, Xiaona (Frontiers in Public Health, 2023)
Environmental pollutants, such as rare earth elements, affect human health, particularly in inducing reproductive system injury. In this study, we found that long-term exposure to YCl3 in rats produced significant pathological changes. YCl3 treatment could induce apoptosis in Leydig cells. In addition, YCl3 enhanced the concentration of cytosolic Ca2+ and up regulated the expression of IP3R1/CaMKII axis in Leydig cells. However, inhibition of IP3R1 and CaMKII with 2-APB and KN93, respectively, could reverse these effects, including cell apoptosis. Collectively, long-term exposure to yttrium could induce testicular injury by stimulating cell apoptosis, which might be associated with activation of Ca2+/IP3R1/CaMKII axis in Leydig cells.